ON THE STATE OF NATIONAL RIGHTS AND STRUGGLE FOR THEM IN THE ACTIVITIES OF THE UKRAINIAN PUBLIC GROUP TO PROMOTE THE IMPLEMENTATION OF THE HELSINKI ACCORDS ON HUMAN RIGHTS –THE UKRAINIAN HELSINKI GROUP - Білоус, Л. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The struggle for the Ukrainian people’s national rights in the conditions of soviet totalitarian state during 1970-1980ss as one of the trends of the activities of the Ukrainian Public Group to promote the Implementation of the Helsinki Accords on Human Rights and its successor the Ukrainian Helsinki Group is being analyzed.